Carbohydrate antigen 19‐9 is a prognostic and predictive biomarker in patients with advanced pancreatic cancer who receive gemcitabine‐containing chemotherapy. Issue 2 (11th July 2012) - Bauer, Todd M.; El‐Rayes, Bassel F.; Li, Xiaobai; Hammad, Nazik; Philip, Philip A.; Shields, Anthony F.; Zalupski, Mark M.; Bekaii‐Saab, Tanios
Abstract BACKGROUND: Carbohydrate antigen 19‐9 (CA19‐9) is a widely used biomarker in pancreatic cancer. There is no consensus on the interpretation of the change in CA19‐9 serum levels and its role in the clinical management of patients with pancreatic cancer. METHODS: Individual patient data from 6 prospective trials evaluating gemcitabine‐containing regimens from 3 different institutions were pooled. CA19‐9 values were obtained at baseline and after successive cycles of treatment. The objective of this study was to correlate a decline in CA19‐9 with outcomes while undergoing treatment. RESULTS: A total of 212 patients with locally advanced (n = 50) or metastatic (n = 162) adenocarcinoma of the pancreas were included. Median baseline CA19‐9 level was 1077 ng/mL (range, 15‐492, 241 ng/mL). Groups were divided into those levels below (low) or above (high) the median. Median overall survival (mOS) was 8.7 versus 5.2 months (P = .0018) and median time to progression (mTTP) was 5.8 versus 3.7 months (P = .082) in the low versus high groups, respectively. After 2 cycles of chemotherapy, up to a 5% increase versus ≥ 5% increase in CA19‐9 levels conferred an improved mOS (10.3 vs 5.1 months, P = .0022) and mTTP (7.5 vs 3.5 months, P = 0.0005). CONCLUSIONS: In patients who have advanced pancreatic cancer treated with gemcitabine‐containing regimens baseline CA19‐9 is prognostic for outcome. A decline in CA19‐9 after the second cycle of chemotherapy is not predictive of improved mOS or mTTP; thus, CA19‐9 decline is not a useful surrogate endpoint in clinical trials. Clinically, a ≥ 5% rise in CA19‐9 after 2 cycles of chemotherapy serves as a negative predictive marker. Cancer 2013. © 2012 American Cancer Society.